Design of Enterprise Information System with TOGAF Framework (Case Study: STD Bali) - Murpratiwi, Santi Ika; Gustina, Angelina Widya; Dewi, Indah Cahya (International Journal of Engineering and Emerging Technology; Vol 1 No 1 (2016): July - December)
The purpose of this study is to design enterprise architecture at universities in order to improve service to external parties and internal organization. In this study, the methodology of The Open Group Architecture Framework Architecture Development Method (TOGAF ADM) is used. Research enterprise information system design in Bali to discuss STD enterprise architecture to migration planning stage. The result of this research is the design of information systems for each sub-unit business with the main goal of improving performance in every sub-organizations to produce information that is relevant, accurate and timely. This study produced an information systems architecture blueprint candidates application form for each sub-organization ordered according to priority needs so that the implementation of more focused and does not interfere with the performance of information systems either already exist or are being built. On the results of the mapping are 4 main systems Academic Information Systems, Admission Information Systems, Providing Education, Graduation, Alumni and Career Information System. There are also four support systems that the financial management system, employee payroll system, technical services information system and general affairs information system.